The doublecortin-family kinase ZYG-8DCLK1 regulates microtubule dynamics and motor-driven forces to promote the stability of C. elegans acentrosomal spindles. - Emily R Czajkowski; Yuntong Zou; Nikita S Divekar; Sarah M Wignall (PLoS Genetics, 2024)
Although centrosomes help organize spindles in most cell types, oocytes of most species lack these structures. During acentrosomal spindle assembly in C. elegans oocytes, microtubule minus ends are sorted outwards away from the chromosomes where they form poles, but then these outward forces must be balanced to form a stable bipolar structure. Simultaneously, microtubule dynamics must be precisely controlled to maintain spindle length and organization. How forces and dynamics are tuned to create a stable bipolar structure is poorly understood. Here, we have gained insight into this question through studies of ZYG-8, a conserved doublecortin-family kinase; the mammalian homolog of this microtubule-associated protein is upregulated in many cancers and has been implicated in cell division, but the mechanisms by which it functions are poorly understood. We found that ZYG-8 depletion from oocytes resulted in overelongated spindles with pole and midspindle defects. Importantly, experiments with monopolar spindles revealed that ZYG-8 depletion led to excess outward forces within the spindle and suggested a potential role for this protein in regulating the force-generating motor BMK-1/kinesin-5. Further, we found that ZYG-8 is also required for proper microtubule dynamics within the oocyte spindle and that kinase activity is required for its function during both meiosis and mitosis. Altogether, our findings reveal new roles for ZYG-8 in oocytes and provide insights into how acentrosomal spindles are stabilized to promote faithful meiosis.